Comprehensive CSF Tau Profiling Identifies Soluble Tau Pathophysiological Stages in Dominantly Inherited Alzheimer Network (DIAN): Implications for the DIAN‐TU Tau Next Generation Platform. (20th December 2022) - Horie, Kanta; Barthélemy, Nicolas R.; Li, Yan; Sato, Chihiro; Gordon, Brian A.; Benzinger, Tammie L.S.; Sachdev, Pallavi; McDade, Eric; Bateman, Randall J.
Abstract: Background: Brain tau aggregation is a pathological hallmark of Alzheimer's disease (AD) and the tau microtubule binding region (MTBR) is the core of AD tau tangles. Recently, we identified the enrichment of some specific MTBR species in sporadic AD brain tangles. Corresponding soluble MTBR species in the CSF increased together with clinical progression and tau pathology measured by tau‐PET. Because extracellular MTBR‐tau was discovered in human AD, MTBR‐tau has become a high priority target for antibodies binding this region. In this study, we sought to determine when these MTBR‐tau changes occurred and the relationship to clinical, cognitive and biomarker changes in the DIAN. Method: We designed a mass spectrometry‐based method to quantify more than a dozen tau species in CSF. To profile MTBR‐tau, we conducted the immunoprecipitation using the anti‐MTBR antibody, E2814 which is bi‐epitopic to R2 and R4 regions and a tau drug in clinical trial. We analyzed CSF from 227 mutation carriers (MCs) (152 asymptomatic, 77 symptomatic) and 141 non‐carriers enrolled in the DIAN‐observational cohort. Result: CSF MTBR‐tau specifically increased in MCs and changed at different times over the disease course. The change of MTBR‐tau299 (residue 299‐317) in R2‐3 occurred at an estimated years to symptom onset (EYO) of −22, close to the first detection of change in p‐tau217 occupancy (EYO −21). The increase of MTBR‐tau354 (residue 354‐369) in R4 saturated in late clinical stages, potentially due to the deposition into brain tangles. Notably, the ratio of MTBR‐tau299/354 which expected to recapitulate tau pathophysiology highly correlated with p‐tau217 occupancy, an early amyloid marker, in especially asymptomatic MCs (r = 0.82). This indicates MTBR‐tau and p‐tau217 could be useful as biomarkers to assess anti‐MTBR therapies in tau‐PET negative populations. Conclusion: We identified a soluble measure of tau tangles, CSF MTBR species, with changes many years before symptom onset and continuing through symptomatic stages, suggesting early pre‐symptomatic prevention trials can be implemented with anti‐MTBR‐tau antibodies, such as E2814. These results have been utilized to design the tau next generation platform in the DIAN Trials Unit (DIAN‐TU) E2814 drug arm to target soluble MTBR‐tau in independent cohorts of asymptomatic and symptomatic mutation carriers.